A survey of searching and information extraction on a classical text using ontology-based semantics modeling: a case of Quran - Ahmad, Omar; Hyder, Irfan; Iqbal, Rizwan; Azmi Murad, Masrah Azrifah; Mustapha, Aida; Mohd Sharef, Nurfadhlina; Mansoor, Muhammad (Marsland Press, 2013)
Quran is the religious text of Islam. Followers of Islam believe that it is the verbatim word of Allah (God). In the last few years, the Quran has become a target of interest for researchers in the field of computer science, for exploring the divine knowledge encapsulated in it. Since the last few years ontologies have gained significant importance in computer science research because of its machine understandable and semantic nature. Ontologies play an important role in supporting the notion of the semantic web. Some work has been done on the Quran exploiting the platform of ontologies. This paper presents a survey based on recent works which uses ontologies as a means of representing and encapsulating the knowledge of the Quran. In order to compare the reviewed literature, an authentic framework is used which is applicable to any ontology application. Furthermore, the paper includes a comprehensive comparison table based on the framework which allows the readers to understand the details of all works in a glance. At the end of the paper, the conclusion and future work section highlights the shortcomings of the existing works and give a sense of direction to aspiring researchers in order to contribute to the domain of the Quran.